PENGEMBANGAN BAHAN AJAR MENGGUNAKAN METODE GUIDE READING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KRITIS KELAS IV SEKOLAH DASAR - Yuniarti; Abdul Muktadir; Agus Susanta (Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to develop: teaching materials using the guided reading method to improve critical reading skills in grade IV elementary school. This research is research and development using the ADDIE model, namely the analysis, design, development, implementation and evaluation stages. The research object is teaching materials using the guided reading method. The instruments used were feasibility test questionnaires and student response questionnaires and teacher interview guidelines. The feasibility test was carried out by 6 validators, namely 2 material experts, 2 language experts and 2 presentation experts. User response testing was carried out on 20 class IV students and 1 class teacher at SDN71 Bengkulu City. Data analysis is used to determine the validity of teaching materials using cross tabulation and distribution of questionnaires for student responses and interviews for teacher responses in the use of teaching materials. Percentage technique and processed descriptively. The results of the feasibility test of teaching materials by the validator were reviewed from the material, language and presentation aspects, the material feasibility was 0.80 (feasible criteria), the language feasibility results were 0.70 (feasible criteria) and the appearance feasibility results were 0.90 (very feasible criteria) . The results of the field test of teaching materials by carrying out post tests and pre tests with the gain test results showing 20 students with a high criteria gain count of 5 students with a percentage of 25% then medium criteria 13 students with a percentage of 65% then low criteria 2 students with a percentage 10%. Apart from that, the results of interviews with class IV teachers showed a positive response. In other words, the teaching materials used are beneficial and effective for use as supporting teaching materials in improving critical reading skillsls.